Clinical Accuracy of 3D-Planned Maxillary Positioning Using CAD/CAM-Generated Splints in Combination With Temporary Mandibular Fixation in Bimaxillary Orthognathic Surgery. Issue 4 (December 2020) - Pietzka, S.; Mascha, F.; Winter, K.; Kämmerer, P. W.; Sakkas, A.; Schramm, A.; Wilde, F.
Study Design: The aim of this study was to evaluate the accuracy of 3-dimensional (3D)-planned maxillary positioning by using computer-assisted design (CAD)/computer-assisted manufacturing (CAM) splints combined with temporary mandibular fixation in bimaxillary orthognathic surgery. In orthognathic surgery, customized splints work sufficiently well to transfer preoperative planning into the operation site for transverse und sagittal positioning of the maxilla. The vertical positioning is more difficult due to the non-fixed mandibular reference. Therefore, the combined use of CAD/CAM splints and temporary mandibular fixation to the zygomatic region was applied for transferring the 3D-planned maxillary position into the operation site from 2012 until 2015 in our hospital. Objective: In addition to the general accuracy, the precision should therefore be checked especially in the vertical plane compared to axial and sagittal plane. Methods: In this retrospective study, we calculated the deviation of 5 occlusal landmarks of the maxilla in 35 consecutive patients by fusing preoperative 3D planning images and postoperative computed tomography scans after bimaxillary surgery. Results: The overall median deviation of maxillary positioning between plan and surgical result was 0.99 mm. The accuracy of left–right positioning was median 0.96 mm. Anterior–posterior positioning of the maxilla showed a median accuracy of 0.94 mm. Just slightly higher values were determined for the upward–downward positioning (median 1.06 mm). Conclusions: This demonstrates the predictability of maxillary positioning by using CAD/CAM splints in combination with temporary mandibular fixation in all 3 axes.